Feasibility of administrative data for studying complications after hip fracture surgery. Issue 4 (4th May 2017) - Sheehan, Katie Jane; Sobolev, Boris; Guy, Pierre; Tang, Michael; Kuramoto, Lisa; Belmont, Philip; Blair, James A; Sirett, Susan; Morin, Suzanne N; Griesdale, Donald; Jaglal, Susan; Bohm, Eric; et al.
Abstract : Purpose: There is limited information in administrative databases on the occurrence of serious but treatable complications after hip fracture surgery. This study sought to determine the feasibility of identifying the occurrence of serious but treatable complications after hip fracture surgery from discharge abstracts by applying the Agency for Healthcare Research and Quality (AHRQ) Patient Safety Indicator 4 (PSI-4) case-finding tool. Methods: We obtained Canadian Institute for Health Information discharge abstracts for patients 65 years or older, who were surgically treated for non-pathological first hip fracture between 1 January 2004 and 31 December 2012 in Canada, except for Quebec. We applied specifications of AHRQ Patient Safety Indicators 04, Version 5.0 to identify complications from hip fracture discharge abstracts. Results: Out of 153 613 patients admitted with hip fracture, we identified 12 383 (8.1%) patients with at least one postsurgical complication. From patients with postsurgical complications, we identified 3066 (24.8%) patient admissions to intensive care unit. Overall, 7487 (4.9%) patients developed pneumonia, 1664 (1.1%) developed shock/myocardial infarction, 651 (0.4%) developed sepsis, 1862 (1.1%) developed deep venous thrombosis/pulmonary embolism and 1919 (1.3%) developed gastrointestinal haemorrhage/acute ulcer. Conclusions: We report that 8.1% of patients developed at least one inhospital complication after hip fracture surgery in Canada between 2004 and 2012. The AHRQ PSI-4 case-finding tool can be considered to identify these serious complications for evaluation of postsurgical care after hip fracture.